Transforming the journey together: Baseline findings from a longitudinal, co-designed study on psychiatry trainee experiences of training and wellbeing. (June 2022) - Orlik, Stefanie; Barnes, Caryl; Karageorge, Aspasia; You, Daniel; McLean, Loyola M; Proctor, Marie-Therese; Kornhaber, Rachel; Nash, Louise
Objective: Junior doctors have high rates of burnout resulting in downstream impacts on patient care. The aim of this study is to capture cross-sectional data on a cohort of psychiatry trainees. These data will be used to inform a wider project investigating psychiatry trainee mental health and wellbeing. Method: This paper reports on the 2019 baseline data of psychiatry trainees enrolled in a formal education course at the University of Sydney, Australia. The data were collected with an online survey using a range of validated mental health and wellbeing scales. This descriptive study involved psychiatry trainees as co-designers. Results: Our research findings are in keeping with the existing literature on the poor mental health and wellbeing of doctors with significantly higher levels of anxiety and exhaustion found in female trainees and carers. Despite this, the cohort had high scores on the flourishing scale. Conclusions: Concern around the wellbeing of junior doctors in Australia appears justified. We need to move beyond focussing on individual action to systems-based approaches to improving wellbeing and ongoing sustainability of the psychiatry trainee workforce in NSW.